Pengaruh Penambahan Bubuk Agar sebagai Bahan Pengental terhadap Karakteristik Fisik, Kimia, dan Sensori Dodol Pepaya (Carica papaya L.) - Tjhang Winny Kurniawan; Welly Deglas (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2023)
The purpose of this study was to determine the effect of adding agar powder as a thickener to the physical, chemical, and sensory characteristics of papaya dodol and to determine the water content, vitamin C, and organoleptic content of papaya dodol by adding agar powder as a thickener to the physical, chemical characteristics, and sensory lunkhead papaya. The research method used was a completely randomized design (CRD) with three replications with the addition of agar powder, namely control without the addition of 0% P1 agar powder, 3% P2 agar powder, 5% P3 agar powder and 7% P4 agar powder. In this study the parameters observed were water content, vitamin C, and organoleptic properties of papaya dodol with the addition of agar powder as a thickener to the physical, chemical, and sensory characteristics of papaya dodol. The addition of agar powder in the manufacture of papaya dodol increases the water content in the product. In addition, agar powder can also protect vitamin C during the processing, although it still suffers damage when heated. The use of agar powder also gives a significantly different chewy texture to papaya dodol. However, the agar powder did not have a significant effect on the color, aroma, and taste of the papaya dodol, because the papaya dodol aroma was stronger and more dominant, while the agar powder had no taste and its gelatinous nature did not affect the change in the taste of the papaya dodol.